Improving Voltage Profile of Islanded Microgrid using PI Controller - Sajid Hussain Qazi; Mohd Wazir Mustafa (Institute of Advanced Engineering and Science, 2018)
In islanding operating mode of microgrid, the voltage and frequency of system must be maintained by the microgrid, or else the system will crumble due to the characteristics of different distributed generators (DG) utilized in microgrid. The voltage and frequency lost provision when main grid is disconnected. This paper presents PI controller based voltage controller to regulate voltage to its normal condition. The controller is proposed to be utilized individually with each distributed generator (DG) in microgrid. The controller compares inverter output voltage with voltage at point of common coupling (PCC) and its output is feed to PWM pulse generator to generate appropriate pulses for inverter to regulate voltage to its nominal value. The simulation results of proposed system are shown using MATLAB/Simulink platform.